Characterization of soluble and insoluble fractions obtained from a commercial pea protein isolate - Moll, Pascal; Salminen, Hanna; Seitz, Oskar; Schmitt, Christophe; Weiss, Jochen (Journal of dispersion science and technology, 2023)
In this study, the characteristics of pea protein isolates after aqueous fractionization into water-soluble and water-insoluble fractions by centrifugation, decantation, and lyophilization were studied. Chemical composition and physicochemical properties upon pH changes were determined. The overall protein compositions of both soluble and insoluble pea protein fractions were similar containing albumins, globulins, and lipoxygenases, but amino acid compositions slightly varied. Distinct differences were observed in their charge properties, particle sizes, and voluminosities. The soluble pea protein fraction was free of measurable particles at pH 7, whereas the insoluble proteins contained particles with sizes of > 80 µm. Close to their respective isoelectric points, the soluble (pI = 3.9) and insoluble pea proteins (pI = 4.9) had very similar sizes of 40-50 µm. At pH 3, the particle sizes of soluble proteins did not change, however, the insoluble pea proteins had again sizes of > 80 µm. Voluminosity of the insoluble fraction was pH-dependent and had its highest voluminosity at pH 3 and 7, indicating changes in water binding as a function of pH. In contrast, the voluminosity of the soluble pea protein fraction did not change with pH. Taken together, this study showed that water-soluble and insoluble pea protein fractions of a commercial isolate may differ substantially with respect to their physicochemical properties. Observed inconsistencies in technofunctionality of various commercial preparations could thus be promoted by varying ratios between the two fractions.